PENGABDIAN KEPADA MASYARAKAT BAGI NELAYAN NAMBANGAN KELURAHAN KEDUNG COWEK KECAMATAN BULAK “PENYULUHAN PERAWATAN MESIN KAPAL NELAYAN” - Syamsuri; Miftahul Ulum; Bambang Setyono; Suheni; Dwi Khusna; Gatot Setyono; Ardi Noerpamoengkas; Desmas Arifianto P; Vuri Ayu S; Ahmad Yusuf I; Hery Irawan; Hasan Syafik M (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Fishing at sea is part of the livelihood of coastal communities. In the sea conditions there are a lot of obstacles experienced by fishermen, one of which is when the engine experiences lose compression which causes the engine to die so that fishermen will find it difficult to change positions or if they want to land. For this reason, this community service done to help the fishermen in knowing the symptoms and disturbance experienced by the engines that they use on the ship by taking care as well as maintenance that will be done when they encounter problems. The coastal community of nambangan is one of the economic centers in the marine sector that produces a variety of processed seafood both food and decoration located in Surabaya. From field observations and direct interviews with the head of the local fishing community, there were three focusses aspects of this community service program, namely the engine problems, troubleshooting, and the engine maintenance. The counseling, was hoped that the fishermen will be able to understand and maintenance the condition of their ship's engine in order to minimize obstacles when they are at sea. And also to increase their sea products food and processed seafood products in order to meet consumer demand.